2010
DOI: 10.1158/0008-5472.sabcs10-pd04-02
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD04-02: Clinical Value of Circulating Tumor Cells (CTC) in First Line Metastatic Breast Cancer (MBC) Patients (pts) According to Type of Treatment and Immunohistochemical Molecular Subtype

Abstract: Background: The detection of more than 5 CTCs/7.5 ml of blood in MBC pts predicts worse progression-free survival (PFS) and overall survival (OS). We investigated time-related clinical trend of CTCs according to types of 1st line therapy (hormonal therapy, HTx; chemotherapy CTx, anti-HER2 therapy; CTx with Bevacizumab) and immunohistochemical (IHC) subtypes of disease. Methods: Enumeration of CTCs was performed by the CellSearch™ technology as standard of care for 235 MBC pts receiving 1st line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…as a noninvasive means of predicting and monitoring response to treatment in metastatic disease, has recently been comprehensively discussed by Alix-Panabieres and Pantel [ 25 ]. Unsuccessful regimens could be abandoned early in favor of alternative regimens, thus sparing patients unnecessary toxicity [ 6 - 8 ]. Moreover, in the future real-time CTC enumeration during therapy should be complemented by additional markers, which enable the monitoring of those cells which possess the highest metastasis-inducing activity within the highly heterogeneous pool of EpCAM+ CTCs [ 4 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as a noninvasive means of predicting and monitoring response to treatment in metastatic disease, has recently been comprehensively discussed by Alix-Panabieres and Pantel [ 25 ]. Unsuccessful regimens could be abandoned early in favor of alternative regimens, thus sparing patients unnecessary toxicity [ 6 - 8 ]. Moreover, in the future real-time CTC enumeration during therapy should be complemented by additional markers, which enable the monitoring of those cells which possess the highest metastasis-inducing activity within the highly heterogeneous pool of EpCAM+ CTCs [ 4 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prognostic information of ≥ 5 CTCs/7.5 ml blood might be helpful in identifying those patients who would likely experience a worse outcome with standard treatment and might benefit from more aggressive therapy [ 4 ]. Thus far, several retrospective and a few prospective studies in patients with MBC have demonstrated the usefulness of monitoring therapeutic efficacy by serial CTC enumerations [ 6 - 9 ]. To further address this important issue, the present study aimed to prospectively assess in a large group of patients whether CTC status at baseline (CTC BL ) and after one cycle of a new line of treatment (CTC 1C ) and changes in CTC status from baseline to completion of one treatment cycle (CTC kinetics, CTC KIN ) could serve as early predictors of efficacy in terms of response, PFS, and OS.…”
Section: Introductionmentioning
confidence: 99%